Do Brand Competence and Warmth Always Influence Purchase Intention? The Moderating Role of Gender - Xue, Jianping; Zhou, Zhimin; Zhang, Liangbo; Majeed, Salman (Frontiers in Psychology, 2020)
Consumers’ perceptions of a brand (e.g. competence or warmth) may directly affect their brand trust, purchase intention, and ability to achieving corporate goals of sustainability. However, gender acts as a moderator in the influence of brand perception on purchase intention. This study examined the main effects of brand perception on purchase intention, the moderating effect of gender, and the mediating effect of brand trust by conducting two experiments and a path analysis. Findings from experiment 1 show that perceived warmth and perceived competence exert significant positive effects on purchase intention with brand trust as a mediator. Findings from experiment 2 indicate that perceived warmth is influential only for female customers, not for male customers, that is, gender moderates the relationship between perceived warmth and purchase intention. However, gender does not moderate the influence of perceived competence on purchase intention. The results of the path analysis are consistent with the experimental results, indicating that the conclusions of the study are robust and reliable. Finally, theoretical contributions and managerial implications are discussed.